A randomised controlled trial to determine patient experience of a magnetostrictive stack scaler as compared to a piezoelectric scaler, in supportive periodontal therapy. (February 2020) - Daly, Sinead; Newcombe, Robert G.; Claydon, Nicholas C.A.; Seong, Joon; Davies, Maria; West, Nicola X.
Abstract: Objectives: To compare the pain/discomfort experienced by patients in supportive periodontal therapy, following treatment with a piezoelectric ultrasonic scaler, designed for use with warmed water irrigation, and a magnetostrictive ultrasonic scaler. Methods: This was a single-centre, randomised, split mouth study with regard to side, and crossover with regard to treatment order. Patients attending general dental practice for supportive periodontal therapy were randomised to receive treatment from one scaler on the left and the other scaler on the right-hand side of the mouth, the left side of the mouth always being treated first. The piezo scaler (Tigon+®) was used with room temperature irrigation for half of the participants (approx 20 °C) and warmed water irrigation (approx 36 °C) for the other half. The magnetostrictive scaler (Cavitron Select SPS 30K®) was used with room temperature irrigation (approx 20 °C) only. Participants rated their pain/discomfort, noise and vibration by VAS scale. Results: 140 participants completed the study. Mean VAS scores for all measures were significantly better for the piezo scaler used with warm irrigation as compared to the magnetostrictive scaler p < 0.001. When both scalers were used with room temperature irrigant, there were no significant differences in the VAS scores between scalers (pain/discomfort, p = 0.68; noise p = 0.2; vibration p = 0.85). Conclusions: Participants indicated to statistical significance, less pain/discomfort, noise and vibration when the piezo scaler (Tigon+®) device was used with warmed irrigant, compared to the magnetostrictive scaler (Cavitron Select SPS 30K®). There were no significant differences between the instruments when room temperature irrigant was used. Clinical significance: Regular scaling in supportive periodontal therapy, is essential for maintenance of susceptible patients, however it can be painful due to dentine hypersensitivity deterring patients from attending. Using a piezo scaler with warm water improves patient quality of life and subsequent oral health. This may have positive effects on patient attendance. ISRCTN registered: ISRCTN15573995.